Imagining the Future: Future Imagination Training Decreases Delay Discounting Among Internet Addicts and Non-Problematic Users - Li, Hongxia (Frontiers in Psychology, 2021)
To test whether future imagination can reduce the delay discounting rate of the Internet addicts, we recruited 40 Internet addicts (treatment sample) and 39 non-problematic users (control sample). We used a 2 (participant type: individuals with Internet addiction vs. non-problematic users) × 2 (training type: future event imagination training vs. control condition) × 2 (training session: first session vs. final session) mixed-subjects design to test our hypothesis. The participant type and training type were between the subjects and the training session was within the subject. Half of each sample (the Internet addicts and non-problematic users) was randomly assigned to complete five sessions of future imagination training and the other half was assigned to describe some daily events they had observed. We used the Barratt Impulsivity Scale (BIS) and delay discounting task to assess our outcome variable, such as addiction, impulsivity, and delay discounting rate. The results showed that the future imagination training significantly reduced the delay discounting rate (also for impulsivity and addiction) for both the Internet addicts and non-problematic users than the control condition. Besides, the negative effect of future imagination training on the delay discounting rates (for impulsivity and addiction) remained consistent across the five training sessions. These findings suggest that the future imagination training can be a useful approach to reduce the impulsivity among those who are addicted to the Internet.